Potensi inhibisi enzim alfa-Amilase oleh cuka buah belimbing wuluh (Averrhoa Bilimbi L.) sebagai aktivitas antidiabetik in vitro - Imma Fatayati; Febiola Panjaitan; Hendra Budi Sungkawa; Ratih Indrawati; Wahdaniah Wahdaniah (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Diabetes mellitus (DM) is a noncommunicable disease with a high prevalence worldwide. One management strategy for DM involves the control of postprandial glucose levels. Starfruit vinegar (Averrhoa bilimbi L.) is a fermented product containing acetic acid and secondary metabolites, particularly flavonoids, which have the potential to inhibit α-amylase activity, thereby helping to regulate postprandial glucose levels.Objectives: This study aimed to identify the antidiabetic activity of starfruit vinegar by inhibiting α-amylase enzyme activity.Methods: This study utilized an in vitro experimental design and was conducted at the Testing Laboratory of Poltekkes Kemenkes Pontianak from February to June 2025. The treatment groups comprised starfruit (Averrhoa bilimbi) vinegar at concentrations of 3000, 3500, 4000, 4500, and 5000 ppm, each with five replicates (25 samples). The positive control group was treated with acarbose (five samples). α-Amylase inhibitory activity was assessed using the Fuwa method and measured using a UV-Vis spectrophotometer at the maximum absorption wavelength. The IC50  values and statistical analysis were determined using a  linear regression test.Results: Both starfruit vinegar and acarbose significantly inhibited α-amylase, with a p-value of 0,008 (p< 0,05). The IC₅₀ value of starfruit vinegar was 2822 mg/ml, indicating very weak inhibitory activity. However, similar to the positive control, acarbose (2548.463 mg/ml) showed weak inhibitory activity.Conclusion: The significant p-value indicates that star fruit vinegar effectively inhibited α-amylase activity. The IC50 value, comparable to that of acarbose, suggests that star fruit vinegar has potential inhibitory activity similar to that of the positive control and may serve as a natural antidiabetic agent.